2021
DOI: 10.33487/edumaspul.v5i2.1783
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception towards Teacher’s Code-switching in EFL Clasroom: Exploring Pedagogical Functions

Abstract: Code-switching is an inevitable phenomenon that often happens inside a foreign or second English classroom. However, this phenomenon is often treated like the elephant in the room: the teacher recognizes its presence but is never really aware of it. While many studies regarding code-switching topics in EFL classrooms only focus on analyzing the type of teacher's code-switching. This study aims to seek out the pedagogical functions behind the teacher's decision to code-switch and determine the students' percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Amid the ongoing discussion, CS is widely used as an important tool that can benefit students in classrooms. As stated by Wibowo et al (2021) it can affect students' understanding of the material delivered, increase their grades (Husni & Arianto, 2023), encourage active class participation, reduce nervousness, and increase motivation to learn English. Moreover, Rezaee and Fathi (2021) found that the practice of CS in the foreign language classroom has a positive relation with the students' anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
“…Amid the ongoing discussion, CS is widely used as an important tool that can benefit students in classrooms. As stated by Wibowo et al (2021) it can affect students' understanding of the material delivered, increase their grades (Husni & Arianto, 2023), encourage active class participation, reduce nervousness, and increase motivation to learn English. Moreover, Rezaee and Fathi (2021) found that the practice of CS in the foreign language classroom has a positive relation with the students' anxiety levels.…”
Section: Introductionmentioning
confidence: 99%